Handgrip strength, functionality and plasma levels of IL-6 in elderly women - Daniele S. Pereira; Viviane F. Cipriano; Juleimar S. C. Amorim; Bárbara Z. Queiroz; Diogo C. Felício; Leani S. M. Pereira
AbstractIntroduction Aging is associated with a chronic low-grade inflammatory process characterized by an increased production of inflammatory mediators. These elevated levels are predictors for muscle function (sarcopenia) and deterioration of physical performance in the elderly.Objective To investigate the correlation between sarcopenia, functional capacity, and interleukin-6 levels.Materials and methods This cross-sectional study assessed a convenience sample of elderly individuals (n = 130) using a handgrip dynamometer (JAMAR™), and the functional capacity test was performed by sitting and standing. Interleukin-6 levels were determined using high sensitivity ELISA kits. Spearman correlation coefficient was used to assess the correlation between these variables, at a significance level (α) of 0.05.Results There was significant inverse correlation between strength and function (rS = -0.273, p = 0.002) such that elderly individuals with lower peak force took longer to perform the sit-to-stand test, in contrast with the relationship between plasma interleukin-6 levels and strength (rS = -0.043, p = 0.624) or functionality (rS = -0.060, p = 0.501).Conclusion The outcome measures analyzed could predict the decline in muscle strength and functional capacity, and may be indicative of sarcopenia in elderly individuals. There was no correlation between the interleukin-6 levels and the grip strength and functional capacity of the sample investigated.